Deflagrations of localised homogeneous and inhomogeneous hydrogen-air mixtures in enclosures. (17th May 2018) - Makarov, D.; Hooker, P.; Kuznetsov, M.; Molkov, V.
Abstract: Two original models for use as novel tools for the design of hydrogen-air deflagration mitigation systems for equipment and enclosures are presented. The first model describes deflagrations of localised hydrogen-air mixtures in a closed space such as a pressure vessel or a well-sealed building while the second model defines safety requirements for vented deflagrations of localised mixtures in an enclosure. Examples of localised mixtures include 'pockets' of gas within an enclosure as well as stratified gas distributions which are especially relevant to hydrogen releases. The thermodynamic model for closed spaces is validated against experiments available from the literature. This model is used to estimate the maximum hydrogen inventory in a closed space assuming the closed space can withstand a maximum overpressure of 10 kPa without damage (this is typical of many civil structures). The upper limit for hydrogen inventory in a confined space to prevent damage is found to be equivalent to 7.9% of the closed space being filled with 4% hydrogen. If the hydrogen inventory in a closed space is above this upper limit then the explosion has to be mitigated by the venting technique. For the first time an engineering correlation is presented that accounts for the phenomena affecting the overpressure from localised vented deflagrations, i.e. the turbulence generated by the flame front itself, the preferential diffusion in stretched flames, the fractal behaviour of the turbulent flame front surface, the initial flow turbulence in unburnt mixture, and the increase of the flame surface area due to the shape of an enclosure. Validation of the new vented deflagration model developed at Ulster has been carried out against 25 experiments with lean stratified hydrogen-air mixtures performed by the Health and Safety Executive (UK) and Karlsruhe Institute of Technology (Germany). Highlights: Two localised deflagration models for closed and vented enclosure are developed. Models are validated against published experiments and performed in this study. The upper safe inventory limit 0.31% vol (enclosure averaged) is below LFL 4% vol. Mixture within 5% of highest burning velocity determines deflagration overpressure. The correlation for vent sizing of localised deflagrations is developed.